The syntax of the Old English preverbal ge- in the light of the theory of language changes as strengthenings or weakenings - Frančiška Trobevšek-Drobnak (Acta Neophilologica, 1992)
The followmg paper reports on the results of 'the investigation into some aspects of the usage of the Old English preverbal ge- from the point of view of the theory of language changes as strengthenings or weakenings. The investigation served as 'the basis for the author's Ph. D. dissertation (1990).